What to Do With the Kid Who ... : Developing Cooperation, Self-discipline, and Responsibility in the Classroom. - Burke, Kathleen (Kay) B. (SAGE Publications, 2008)
Presents updated research on 19 educational issues, plus 38 strategies and templates to help teachers implement RTI and user-friendly disciplinary approaches in K-12 diverse classrooms.